2018
DOI: 10.1055/s-0038-1657783
|View full text |Cite
|
Sign up to set email alerts
|

New Anticoagulant Agents: Incidence of Adverse Drug Reactions and New Signals Thereof

Abstract: The aim of this study was to evaluate the adverse drug reaction (ADR) incidence rate and new signals thereof for classic compared with new anticoagulants in real-life ambulatory settings. The authors performed an observational cross-sectional study in two cohorts of surveyed patients treated with vitamin K antagonists (VKAs; acenocoumarol or warfarin) or nonvitamin K antagonist oral anticoagulants (NOACs; apixaban, edoxaban, rivaroxaban, dabigatran etexilate). Descriptive, clinical, and ADRs data were reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The general idea that emerges is that their use has a mild effect on any changes in bone metabolism [70,71,72,73,74,75,76,77,78] and there is no significant clinical consequence to date to the extent that they cause a reduction in bone mass or secondary osteoporosis fractures. Comparison with VKAs shows a lower risk of osteoporosis and fractures [79,80].…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general idea that emerges is that their use has a mild effect on any changes in bone metabolism [70,71,72,73,74,75,76,77,78] and there is no significant clinical consequence to date to the extent that they cause a reduction in bone mass or secondary osteoporosis fractures. Comparison with VKAs shows a lower risk of osteoporosis and fractures [79,80].…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
“…Treceño-Lobato et al included a total of 334 patients in a study with the aim to evaluate the adverse drug reaction (ADR) incidence rate for classic compared to new anticoagulants. The most significant result was the osteoporosis risk associated with the consumption of VKAs, with 11 cases recorded in the cohort of these patients versus none in the cohort of patients treated with DOACs, supporting the appropriateness of using DOACs in patients at risk of osteoporotic fractures [80].…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%
“…The patients on unfractionated heparin had the highest fracture incidence, but DOACs had no increased fracture risk. [39,40] In another meta-analysis comparing osteoporotic fractures between VKA and DOAC, it was found that DOAC was associated with lower osteoporotic fractures than VKA in NVAF patients but not for VTE prophylaxis. [38] However, our meta-analysis results are more robust as the sample size was more significant (89,549 vs. 321,844) and comprised of extensive population-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…The patients on unfractionated heparin had the highest fracture incidence, but DOACs had no increased fracture risk. [ 39 , 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…In light of the aspects considered so far, it becomes crucial to detect, assess, understand, and maybe prevent all NOACs ADRs [ 26 ], not just the severe ones, but even the very rare ones, such as body rash, epistaxis, ecchymosis, gingival bleeding and other [ 27 , 28 ] or any negative drug–drug interactions [ 29 , 30 , 31 ] detected in real-world experience, considering, as discussed above, the clinical complexity of patients treated.…”
Section: Introductionmentioning
confidence: 99%